The Relevance Of Hamka’s Tawakkul Framework In Addressing Burnout - Nur Hadi Ihsan; Mohammad Adil Alwi Zaim; M. Najib Abdussalam (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study investigates the potential of Hamka's concept of tawakkul (trust in Allah) as an intervention for workplace burnout syndrome. While existing literature addresses burnout through various psychological interventions, including cognitive behavioral therapy and mindfulness, the Islamic spiritual concept of tawakkul offers a unique perspective that merits exploration. Through qualitative library research, this study analyzes Hamka's seminal work Tasauf Modern alongside contemporary literature on burnout and Islamic psychology. The research examines how tawakkul's core principles of divine dependence, resilience, and gratitude may address the three primary dimensions of burnout: emotional exhaustion, depersonalization, and reduced personal accomplishment. Findings suggest that tawakkul's framework can effectively counteract internal factors contributing to burnout by fostering psychological resilience and spiritual well-being. The integration of tawakkul into modern psychological interventions presents a promising approach for Muslim professionals experiencing workplace burnout, offering a culturally and spiritually aligned coping strategy. This study contributes to the growing body of research on indigenous and spiritual approaches to mental health, demonstrating how traditional Islamic concepts can be integrated into modern psychological interventions for workplace stress management